Ancient Empires - Edited by Brandon, S. G. F (New York The Reader's Digest Association Limited, 1973)
Traces milestones in history from the emergence of Egypt around 3000 B.C. up to the scattering of the Jews in 70 A.D.
IncludeColour Illustrations and Index
Keywords: History, Ancient